TINJAUAN YURIDIS DAMPAK PERKAWINAN DIBAWAH UMUR TERHADAP PERCERAIAN DI INDONESIA - Ludya Sirait (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTIndonesia has rules about arranged marriages in the Act. In The Act one of which regulates the minimum age requirement to marriages. But in reality there are Indonesian citizens who perform marriages under the age of which is set in the Act. Marriage under that age have a devastating effect, one of which is divorce.This study aims to determine the impact of underage marriage and also sanctions applicable in Indonesia for the perpetrators and supporters of underage marriage.Through the research process interview in several places relating to marriage and divorce process, analyze the data obtained from the field and also read some of the literature on various websites and books.Then through the research generated that underage marriage is prohibited by law but can be done using the letter Married dispensation. Divorce percentage is also produced from 2013 through 2014. Keywords : Impact,sanctions, Marriage under the Age, Divorce